(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The first description of the hypopus of Glycyphagus privatus Oud. is given. The species is a typical granary mite which is often present in house dusts. A comparison is also made among the morphology of hypopus of similar species G. domesticus De Geer and G. (=Lepidoglyphus) destructor Schrank.